Pengaruh Metode Role Play terhadap Keterampilan Sosial Emosional Anak 4-5 Tahun - Wuni Arum Sekar Sari; Intan Zakiyah; Briyantika Puji Lestari (Universitas Islam Tribakti Lirboyo Kediri, 2026)
The study aimed to explore how the role-playing approach can foster the social-emotional skills of children aged 4 and 5 years at Perwanida 1 Mrican Kindergarten, Kediri City. This study used a quasi-experimental design with a pretest-posttest control group model and quantitative methodology. Thirty-five children participated, and they were divided into two groups: the experimental group and the control group. Based on early childhood social-emotional development markers, data were collected through observation. Data analysis included homogeneity, normality, and sample t-tests. The findings showed that the experimental group's average pretest score of 37.58 significantly increased to 88.07 in the posttest. However, the control group's score only slightly increased from 38.73 to 40.90. A substantial difference between the two groups was demonstrated by the hypothesis test findings, which showed a significance score <0.001. Therefore, it can be said that the role-playing approach significantly improves the social-emotional skills of children aged 4 to 5 years. This approach has been shown to be successful in increasing children's self-confidence and prosocial behavior, as well as collaboration skills, emotional control, and adherence to rules.